Unusual Presentation of Hydatid Cyst - Mahbub, NAM Golam (TAJ: Journal of Teachers Association, 2009)
Affection of muscle by a hydatid cyst is rare. The clinical diagnosis of a hydatid cyst occurring in muscle is quite difficult. To reach to a diagnosis, a clinician should be cautious in taking proper history, doing necessary physical examinations & some investigations like ultrasonography, blood examination & fine needle aspiration. Removal of the cyst by surgery is the treatment of choice doi: 10.3329/taj.v18i2.3196 TAJ 2005; 18(2): 137-139